Exports and Productivity Growth: First Evidence from a Continuous Treatment Approach - Helmut Fryges; Joachim Wagner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
A recent survey of 54 micro-econometric studies reveals that exporting firms are more productive than non-exporters. On the other hand, previous empirical studies show that exporting does not necessarily improve productivity. One possible reason for this result is that most previous studies are restricted to analysing the relationship between a firm?s export status and the growth of its labour productivity, using the firms? export status as a binary treatment variable and comparing the performance of exporting and non-exporting firms. In this paper, we apply the newly developed generalised propensity score (GPS) methodology that allows for continuous treatment, that is, different levels of the firms? export activities. Using the GPS method and a large panel data set for German manufacturing firms, we estimate the relationship between a firm?s export-sales ratio and its labour productivity growth rate. We find that there is a causal effect of firms? export activities on labour productivity growth. However, exporting improves labour productivity growth only within a subinterval of the range of firms? export-sales ratios.
Keywords: F23; F14; L60; 330; Export-sales ratio; labour productivity; continuous treatment; dose-response function